Mental health, positive affectivity and wellbeing in prison: a comparative study between young and older prisoners - S Chiclana; R Castillo-Gualda; D Paniagua; R Rodríguez-Carvajal (Sociedad Española de Sanidad Penitenciaria, 2020)
ABSTRACT Objectives To explore sociodemographic, psychological and psychopathological characteristics, as well as to evaluate the behaviour in an inmate sample. Materials and methods There is a total sample of 182 young and elderly inmates of the Madrid III Prison. The investigation has been carried out with a battery of self-report psychological questionnaires and objective measurements obtained through the prison files. Comparisons of means were made to see if there are significant differences between the two groups (young and elderly inmates) in the variables analysed. Results The analysis shows that there are no significant differences in wellbeing between young and elderly inmates. However, young people have higher levels of psychological distress, more presence of negative emotions and have a more maladjusted behaviour in prison (they consume more cannabis and have more disciplinary records). Older people better regulate their emotions, adopt better the perspectives of others, showing themselves to be friendlier. Conclusions The elderly inmates in prison, compared with the youngest, have a better psychological adjustment, more internal resources and a better adaptation to the prison environment despite of no differences in related variables such as time in prison.